Protecting of the rights of victims of sexual crimes in Polish criminal procedure - Wszołek, Roksana; Światłowski, Andrzej; Nagy, Anita (Publicationes Universitatis Miskolcinensis, Sectio Juridica et Politica, 2022)
The aim of the article is to describe and discuss Polish legal regulation in the field of sexual offences in order to present and briefly evaluate the protection of the victims of such offences. Sexual offences have assumed importance and attracted interest in both Polish criminal policy and public discourse in recent years. New legal regulations have also been implemented. The instruments introduced in recent years are briefly described and discussed.